2022
DOI: 10.1186/s40733-022-00083-7
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to inhalers and associated factors among adult asthma patients: an outpatient-based study in a tertiary hospital of Rajshahi, Bangladesh

Abstract: Background Adherence to inhaler medication is an important contributor to optimum asthma control along with adequate pharmacotherapy. The objective of the present study was to assess self-reported adherence levels and to identify the potential factors associated with non-adherence to the inhalers among asthma patients. Methods This facility-based cross-sectional study was conducted in the medicine outpatient department of Rajshahi Medical College H… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…While cutoffs for illness duration in most studies ranged from 1–5 years, one study used a 10-year cutoff, reporting better foot care but poorer diet and physical activity among those with a longer illness duration [ 48 ]. Another study conducted in rural settings reported poorer adherence to asthma inhalers in those with prolonged illness [ 52 ]. Both studies were of low quality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While cutoffs for illness duration in most studies ranged from 1–5 years, one study used a 10-year cutoff, reporting better foot care but poorer diet and physical activity among those with a longer illness duration [ 48 ]. Another study conducted in rural settings reported poorer adherence to asthma inhalers in those with prolonged illness [ 52 ]. Both studies were of low quality.…”
Section: Resultsmentioning
confidence: 99%
“…Smoking was associated with poorer self-management in three out of four studies, the only exception being a low-quality study conducted on asthmatic individuals [ 52 ]. Other less commonly observed associations were a lower BMI [ 41 , 45 ] and a positive family history of illness [ 34 ] which were associated with better self-management.…”
Section: Resultsmentioning
confidence: 99%
“…However, up to 70% of asthma patients do not use their inhalers correctly [3] and improper technique is associated with poor asthma control. Furthermore, almost 43% of asthma patients worldwide are nonadherent to their inhaler treatment plan, with some studies suggesting that the rate may be as high as 87% among patients with severe asthma [4]. Digital inhaler systems (DIS) have demonstrated the ability to identify and improve poor inhaler technique and nonadherence to asthma medications, and ultimately improve asthma control [5 ▪ ,6 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%